DNS blocking in PK: bbc.com, instagram.com, medium.com, nytimes.com, pornhub.com +9 more (Pakistan) - Voidly (2026)
CRITICAL severity censorship detected in Pakistan. Confidence: 85%. Data sourced from CensoredPlanet.
Censorship Incident ID: PK-2026-0010
Keywords: censorship; PK; censorship; critical